Arabizi as a New Linguistic Phenomenon: Identity, Ideology, and Language Practices of the Young Arab Generation - Ahmad, Hafizah (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
Arabizi has emerged as one of the most intriguing linguistic phenomena of the modern era, thriving alongside the explosion of information technology in the Middle East. In the hands of the digital generation, language is no longer merely a static means of communication but rather a medium of expression that is constantly evolving amidst the maelstrom of globalization. This shift in the use of standard Arabic was initially triggered by technical constraints; past digital devices had significant limitations in perfectly accommodating the Arabic script. This limitation forced young Arabs to create a creative hybrid writing style now known as Arabizi, in which the Latin alphabet intertwines with numbers to replace Arabic letter sounds not found in Western languages. In practice, Arabizi utilizes the visual similarity between numbers and Arabic characters as a clever adaptation strategy amidst technological transitions. For the younger generation, interacting in cyberspace with Arabizi provides a more fluid, practical, and modern sense of identity than being tied to formal language structures that are often considered rigid. This journal seeks to dissect how Arabizi is not simply a technical matter of typing, but rather a reflection of the complex struggles of identity, ideology, and language practices in cyberspace. The findings of this study indicate that the currents of globalization and the demands of instant communication on social media are the main drivers of this trend’s persistence. However, behind the ease of global connectivity it offers, the increasingly widespread use of Arabizi raises real concerns for the future of authentic Arabic literacy (Fusha) and the fading of formal grammatical structures. Ultimately, Arabizi is a portrait of cultural hybridity, depicting how young people define their identity between the pull of local traditions and the pressures of global modernity. This phenomenon serves as a reminder that language will always be dynamic, but the preservation of linguistic heritage still requires serious attention amidst the unstoppable pace of digitalization.